2018
DOI: 10.1158/2326-6066.cir-17-0183
|View full text |Cite
|
Sign up to set email alerts
|

NK Cell–Specific CDK8 Deletion Enhances Antitumor Responses

Abstract: Cyclin-dependent kinase 8 (CDK8) is a member of the transcription-regulating CDK family. CDK8 activates or represses transcription by associating with the mediator complex or by regulating transcription factors. Oncogenic activity of CDK8 has been demonstrated in several cancer types. Targeting CDK8 represents a potential therapeutic strategy. Because knockdown of CDK8 in a natural killer (NK) cell line enhances cytotoxicity and NK cells provide the first line of immune defense against transformed cells, we as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 44 publications
(46 reference statements)
0
35
0
3
Order By: Relevance
“…These cytokines are involved in proliferation, differentiation/maturation of NK cells and enhance their effector functions ( 36 , 37 ). Pre-activation of NK cells with IL-2 or IL-12, IL-15 and IL-18 results in the generation of NK cells efficient to target and kill tumor cells ( 24 , 38 ). The lower expression of CD107a and IFN-γ synthesis (after IL-2 or IL-12, IL-15, and IL-18 activation) as well as the increased cell death (in the presence of IL-2) in FcRn −/− NK cells, support an impaired response of NK cells to cytokines in an FcRn −/− deprived microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cytokines are involved in proliferation, differentiation/maturation of NK cells and enhance their effector functions ( 36 , 37 ). Pre-activation of NK cells with IL-2 or IL-12, IL-15 and IL-18 results in the generation of NK cells efficient to target and kill tumor cells ( 24 , 38 ). The lower expression of CD107a and IFN-γ synthesis (after IL-2 or IL-12, IL-15, and IL-18 activation) as well as the increased cell death (in the presence of IL-2) in FcRn −/− NK cells, support an impaired response of NK cells to cytokines in an FcRn −/− deprived microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…For in vitro cytotoxicity assays, isolated NK cells were maintained overnight in RPMI 1640 complete medium supplemented with 50 U/ml rhIL2 and mixed at indicated effector: target ratios (10:1, 5:1 and 1:1) with carboxyfluorescein diacetate succinimidyl ester (CFSE, TonboBio) labeled target YAC-1 cells as previously described ( 23 , 24 ). After 4-h of incubation at 37°C, the specific target cell lysis was assessed by flow cytometry ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…CDK8 is a member of the cyclin-dependent kinase family. 22 As a key regulator of the cell cycle, CDK8 was reported to regulate the G1/S phase of the cell cycle by activating Cyclin C. 23,24 In this paper, circ_0005576 knockdown increased CRC cells in G1 phase and decreased cells in S phase. However, the overexpression of CDK8 significantly reversed this effect.…”
Section: Discussionmentioning
confidence: 78%
“…We and others have previously shown that DCA inhibits CDK8 kinase activity with immunomodulatory effects (11,(20)(21)(22)(23). We used two different approaches to validate CDK8 as the Treg-relevant mechanistic target of DCA.…”
Section: Dca Exerts Tolerogenic Effects On Murine and Human Cd4 + T Cmentioning
confidence: 99%
“…We previously showed that c-Jun phosphorylation by CDK8 regulates IL-10 production in innate immune cells (11). Deletion of CDK8 in NK cells enhances cytotoxicity and improves tumor surveillance (20,21). Furthermore, CDK8/19 inhibitors promote Treg differentiation (22,23).…”
Section: Introductionmentioning
confidence: 99%